EFEKTIVITAS KEBIJAKAN KETUK PINTU KUBUR DALAM PENERBITAN AKTA KEMATIAN DI KELURAHAN MAMMINASAE KECAMATAN PALETEANG KAB. PINRANG - Berliana Berliana; Ida Ayu; Umar Nain; Jamaruddin Jamaruddin (Jurnal Pallangga Praja (JPP), 2021)
Population administration service innovation is an action that is currently being implemented bythe Government through the Ministry of Home Affairs, one of which is the GISA (Gerakan IndonesiaSadar Administrasi Kependudukan) innovation. GISA innovations have been implemented invarious regions in Indonesia, ranging from Provinces, Regencies/Cities, Districts to Village. Oneof the innovations implemented by the Dukcapil Office of Pinrang Regency is Ketuk Pintu Kuburpolicy, which is a policy applied to the issuance of death certificates. The purpose of this study wasto determine the level of effectiveness of the Ketuk Pintu Kubur Policy in issuing death certificatesin Mamminasae Village, Paleteang District, Pinrang Regency. The method used is a qualitativeresearch method. Mamminasae sub-district is one of the Village that implements this policy todiscipline people in order to complete death certificate documents. In 2020 only 3 people out of 25death reports already have death certificates, while others only have Letter of Death.